PENGUKURAN VALUE AT RISK PADA ASET PERUSAHAAN DENGAN SIMULASI MONTE CARLO - Yuliah; Leni Triana (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2021)
This research aims to measure the Value at Risk (VaR) at corporate assets PT Telekomunkasi Indonesia Tbk (TLKM) and PT Bank Mandiri (BMRI)  and portofolios that can be formed by the two assets using Monte Carlo simulation method. The data used of daily closing price a period 1 January 2012 to December  2019. The result shows that the VaR value with stand alone risk of TLKM stock with the Monte Carlo Method is 24% and the VaR Value of BMRI stock is 26,5%, BMRI gives the greater risk than TLKM. While the result of the VaR Value with portofolio risk with Monte Carlo method is 21,4%. The VaR with portofolio risk lower than the VaR with stand alone risk, it shows that the divercification can minimize the risk from investmen.